Hot rolled steel plate

The hot rolled steel sheet addresses the balance of high strength, ductility, and shear processability by employing a specific chemical composition and metal structure, resulting in enhanced performance and resistance to cracking during bending.

JP7648952B2Active Publication Date: 2025-03-19NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023555042
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-11
Filing Date
2022-09-14
Publication Date
2025-03-19
Estimated Expiration
2042-09-14

AI Technical Summary

Technical Problem

Existing hot rolled steel sheets lack a balance between high strength, ductility, and shear processability, which is essential for applications in automobiles and other structural members.

Method used

A hot rolled steel sheet with a specific chemical composition and metal structure, including a chemical composition of C: 0.050~0.250%, Si: 0.05~3.00%, Mn: 1.00~4.00%, and controlled residual austenite, ferrite, and pearlite ratios, along with an entropy value of 10.7 or more and an inverse differentialized normalized value of 1.020 or more.

Benefits of technology

The steel sheet achieves high strength, excellent ductility, and improved shear processability, while also suppressing the occurrence of cracks during bending, thereby enhancing its suitability for various industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648952000027
    Figure 0007648952000027
  • Figure 0007648952000028
    Figure 0007648952000028
  • Figure 0007648952000001
    Figure 0007648952000001
Patent Text Reader

Abstract

This hot-rolled steel plate: has a prescribed chemical composition; has a metal structure having, in area%, retained austenite at less than 3.0%, ferrite at at least 15.0% to less than 60.0%, and pearlite at less than 5.0%; has, according to a gray level co-occurrence matrix method, an entropy value obtained by analyzing a SEM image of the metal structure, of 10.7% or more; an inverse differenced normalized value of at least 1.020; a cluster shade value of -8.0 × 105 - 8.0 × 105; an Mn concentration standard deviation of no more than 0.60 mass%; and a tensile strength of 980 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot-rolled steel sheet. Specifically, the present invention relates to a hot-rolled steel sheet that is used by being formed into various shapes by press working or the like, and in particular to a hot-rolled steel sheet that has high strength and a critical sheet thickness reduction rate at break, and also has excellent ductility and shear workability. This application claims priority based on Japanese Patent Application No. 2021-166958, filed on October 11, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, from the viewpoint of protecting the global environment, efforts are being made in many fields to reduce carbon dioxide emissions. Automobile manufacturers are also actively developing technologies to reduce the weight of vehicles in order to improve fuel efficiency. However, reducing the weight of vehicles is not an easy task, as emphasis is also placed on improving crashworthiness to ensure the safety of passengers.

[0003] In order to achieve both weight reduction and crashworthiness, the use of high-strength steel sheets to thin components has been considered. For this reason, there is a strong demand for steel sheets that combine high strength with excellent formability, and several technologies have been proposed to meet these demands. Since there are various processing styles for automotive components, the required formability varies depending on the component to which it is applied, but among them, the critical break thickness reduction rate and ductility are positioned as important indicators of formability. The critical break thickness reduction rate is a value calculated from the thickness of the tensile test piece before fracture and the minimum value of the thickness of the tensile test piece after fracture. If the critical break thickness reduction rate is low, it is undesirable because it is prone to early fracture when tensile strain is applied during press forming.

[0004] Automotive components are formed by press molding, and the blanks for press molding are often produced by shearing, which has high productivity. Blanks produced by shearing must have excellent end surface accuracy after shearing.

[0005] For example, if a secondary shear surface occurs in the end surface (sheared end surface) after shearing, which is a shear surface-fracture surface-shear surface, the accuracy of the sheared end surface will be significantly degraded.

[0006] For example, Patent Document 1 discloses a hot-rolled steel sheet in which the Mn segregation degree and the P segregation degree at the center of the sheet thickness are controlled, and which serves as a raw material for a cold-rolled steel sheet having excellent surface properties after press working. However, Patent Document 1 does not take into consideration the critical sheet thickness reduction rate at break and the shear workability of the hot-rolled steel sheet. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2020 / 044445 [Non-patent literature]

[0008] [Non-Patent Document 1] J. Webel, J. Gola, D. Britz, F. Mucklich, Materials Characterization 144 (2018) 584-596 [Non-Patent Document 2] DL Naik, HU Sajid, R. Kiran, Metals 2019, 9, 546 [Non-Patent Document 3] K. Zuiderveld, Contrast Limited Adaptive Histogram Equalization, Chapter VIII.5, Graphics Gems IV. PS Heckbert (Eds.), Cambridge, MA, Academic Press, 1994, pp. 474-485 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a hot-rolled steel sheet having high strength and a critical sheet thickness reduction rate at fracture as well as excellent ductility and shear workability. [Means for solving the problem]

[0010] The gist of the present invention is as follows. (1) A hot-rolled steel sheet according to one aspect of the present invention has a chemical composition, in mass%, C: 0.050~0.250%, Si: 0.05 to 3.00%, Mn: 1.00-4.00%, Sol.Al: 0.001-2.000%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Ti: 0 to 0.500%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0-2.00%, Cr: 0-2.00%, Mo: 0-1.00%, Ni: 0-2.00%, B: 0~0.0100%, Ca: 0 to 0.0200%, Mg: 0 to 0.0200%, REM: 0~0.1000%, Bi: 0 to 0.0200%, As: 0~0.100%, Zr: 0-1.00%, Co: 0-1.00%, Zn: 0-1.00%, W: 0 to 1.00%, Sn: 0 to 0.05%, and The balance is Fe and impurities. Satisfying the following formulas (A) and (B), The metal structure is, in area%, The retained austenite is less than 3.0%. Ferrite is 15.0% or more and less than 60.0%; Pearlite is less than 5.0%; The entropy value, which is obtained by analyzing the SEM image of the metal structure by a gray level co-occurrence matrix method and is represented by the following formula (1), is 10.7 or more, The inverse differenced normalized value shown by the following formula (2) is 1.020 or more, The Cluster Shade value shown in the following formula (3) is -8.0×10 5 ~8.0×10 5 and The standard deviation of the Mn concentration is 0.60 mass% or less; The tensile strength is 980MPa or more. 0.060%≦Ti+Nb+V≦0.500% …(A) Zr+Co+Zn+W≦1.00% …(B) However, each element symbol in the formulas (A) and (B) indicates the content of the element in mass %, and 0% is substituted when the element is not contained. Here, P(i,j) in the following formulas (1) to (5) is a gray level co-occurrence matrix, L in the following formula (2) is the number of possible gray scale levels of the SEM image, i and j in the following formulas (2) and (3) are natural numbers from 1 to L, and μ in the following formula (3) is x and μ y are expressed by the following equations (4) and (5), respectively.

number

number

number

number

number

[0011] According to the above-mentioned aspect of the present invention, it is possible to obtain a hot-rolled steel sheet having high strength and a critical thickness reduction rate at fracture, as well as excellent ductility and shear workability. Also, according to the above-mentioned preferred aspect of the present invention, it is possible to obtain a hot-rolled steel sheet having the above-mentioned properties and further suppressing the occurrence of internal cracks in bending, i.e., having excellent resistance to internal cracks in bending. The hot-rolled steel sheet according to the above aspect of the present invention is suitable as an industrial material used for automobile parts, machine structural parts, and further building parts. [Brief description of the drawings]

[0012] [Figure 1] 1 is an example of a sheared end surface of a hot-rolled steel sheet according to an example of the present invention. [Diagram 2] 1 is an example of a sheared end surface of a hot-rolled steel sheet according to a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The chemical composition and metal structure of the hot-rolled steel sheet according to this embodiment will be described in more detail below. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0014] In the following, the numerical ranges described with "~" include the lower and upper limits. Numerical values ​​indicated as "less than" or "greater than" are not included in the numerical range. In the following description, % regarding chemical composition is mass % unless otherwise specified.

[0015] chemical composition The chemical composition of the hot-rolled steel sheet according to this embodiment will be described in detail below.

[0016] C: 0.050~0.250% C increases the area ratio of the hard phase and also increases the strength of ferrite by combining with precipitation strengthening elements such as Ti, Nb, and V. If the C content is less than 0.050%, the desired strength cannot be obtained. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.060% or more, more preferably 0.070% or more, and even more preferably 0.080% or more or 0.090% or more. On the other hand, if the C content exceeds 0.250%, the area ratio of ferrite decreases, and the ductility of the hot-rolled steel sheet decreases. Therefore, the C content is set to 0.250% or less. The C content is preferably 0.200% or less, 0.150% or less, or 0.120% or less.

[0017] Silicon: 0.05 to 3.00% Si has the effect of promoting the formation of ferrite to improve the ductility of the hot-rolled steel sheet, and the effect of solid-solution strengthening ferrite to increase the strength of the hot-rolled steel sheet. Si also has the effect of improving the soundness of the steel by deoxidization (suppressing the occurrence of defects such as blowholes in the steel). If the Si content is less than 0.05%, the above effects cannot be obtained. Therefore, the Si content is set to 0.05% or more. The Si content is preferably 0.50% or more, more preferably 0.80% or more, 1.00% or more, 1.20% or more, or 1.40% or more. However, if the Si content exceeds 3.00%, the surface properties and chemical conversion treatability of the steel sheet, as well as its ductility and weldability, are significantly deteriorated, and the A3 transformation point is significantly increased. This makes it difficult to perform stable hot rolling. In addition, austenite is more likely to remain after cooling, and the critical fracture thickness reduction rate is reduced. Therefore, the Si content is set to 3.00% or less. The Si content is preferably 2.70% or less, more preferably 2.50% or less, 2.20% or less, 2.00% or less, or 1.80% or less.

[0018] Mn: 1.00-4.00% Mn has the effect of suppressing ferrite transformation and increasing the strength of hot-rolled steel sheet. If the Mn content is less than 1.00%, the desired strength cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.30% or more, more preferably 1.50% or more or 1.80% or more. On the other hand, if the Mn content exceeds 4.00%, the hard phase has a periodic band shape due to segregation of Mn, making it difficult to obtain the desired shear workability. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.70% or less or 3.50% or less, more preferably 3.20% or less, 3.00% or less, or 2.60% or less.

[0019] Ti:0~0.500%, Nb:0~0.500%, V:0~0.500% 0.060%≦Ti+Nb+V≦0.500% …(A) However, each element symbol in the formula (A) indicates the content of the element in mass %, and 0% is substituted when the element is not contained. Ti, Nb and V are elements that finely precipitate in steel as carbides and nitrides, and improve the strength of steel by precipitation strengthening. If the total content of Ti, Nb and V is less than 0.060%, these effects cannot be obtained. Therefore, the total content of Ti, Nb and V is set to 0.060% or more. That is, the value of the middle part of the formula (A) is set to 0.060% or more. It is not necessary to contain all of Ti, Nb and V, and it is sufficient that any one of them is contained, and the total content is 0.060% or more. Therefore, the lower limit of the content of Ti, Nb and V is 0%. The lower limit of the content of Ti, Nb and V may be 0.001%, 0.010%, 0.030% or 0.050%, respectively. The total content of Ti, Nb and V is preferably 0.080% or more, more preferably 0.100% or more. On the other hand, if the content of any one of Ti, Nb and V exceeds 0.500%, or if the total content of Ti, Nb and V exceeds 0.500%, the workability of the hot-rolled steel sheet is deteriorated. Therefore, the content of each of Ti, Nb and V is set to 0.500% or less, and the total content of Ti, Nb and V is set to 0.500% or less. That is, the value of the middle part of the formula (A) is set to 0.500% or less. The content of each of Ti, Nb and V is preferably 0.400% or less or 0.300% or less, more preferably 0.250% or less, and even more preferably 0.200% or less or 0.100% or less. The total content of Ti, Nb and V is preferably 0.300% or less, more preferably 0.250% or less, and even more preferably 0.200% or less.

[0020] Sol.Al: 0.001-2.000% Like Si, Al has the effect of deoxidizing steel to improve its soundness, and also has the effect of promoting the formation of ferrite and increasing the ductility of hot-rolled steel sheets. If the sol.Al content is less than 0.001%, the above effects cannot be obtained. Therefore, the sol.Al content is set to 0.001% or more. The sol.Al content is preferably 0.010% or more, 0.030% or more, or 0.050% or more, and more preferably 0.080% or more, 0.100% or more, or 0.150% or more. On the other hand, if the sol.Al content exceeds 2.000%, the above effects are saturated and it is economically undesirable, so the sol.Al content is set to 2.000% or less. The sol.Al content is preferably 1.700% or less or 1.500% or less, more preferably 1.300% or less, and even more preferably 1.000% or less. Incidentally, sol. Al means acid-soluble Al, and indicates solute Al that is present in the steel in a solid solution state.

[0021] P:0.100% or less P is an element that is generally contained as an impurity, but it also has the effect of increasing the strength of hot-rolled steel sheets by solid solution strengthening. The lower limit of the P content is 0%, but P may be actively contained. However, P is an element that easily segregates, and if the P content exceeds 0.100%, the ductility and the critical break thickness reduction rate of the hot-rolled steel sheet due to grain boundary segregation will decrease significantly. Therefore, the P content is set to 0.100% or less. The P content is preferably 0.050% or less, 0.030% or less, 0.020% or less, or 0.015% or less. There is no need to specify the lower limit of the P content, but the lower limit of the P content is 0%. From the viewpoint of refining costs, the lower limit of the P content may be 0.001%, 0.003%, or 0.005%.

[0022] S: 0.0300% or less S is an element contained as an impurity, and forms sulfide-based inclusions in steel to reduce the ductility and the critical thickness reduction rate of a hot-rolled steel sheet. If the S content exceeds 0.0300%, the ductility and the critical thickness reduction rate of a hot-rolled steel sheet are significantly reduced. Therefore, the S content is set to 0.0300% or less. The S content is preferably 0.0100% or less, 0.0070% or less, or 0.0050% or less. The lower limit of the S content is 0%, but may be 0.0001%, 0.0005%, 0.0010%, or 0.0020% from the viewpoint of refining costs.

[0023] N: 0.1000% or less N is an element contained in steel as an impurity, and has the effect of reducing the ductility and the critical thickness reduction rate at break of a hot-rolled steel sheet. If the N content exceeds 0.1000%, the ductility and the critical thickness reduction rate at break of a hot-rolled steel sheet are significantly reduced. Therefore, the N content is set to 0.1000% or less. The N content is preferably 0.0800% or less, more preferably 0.0700% or less or 0.0300% or less, and even more preferably 0.0150% or less or 0.0100% or less. The lower limit of the N content is 0%, but when one or more of Ti, Nb, and V are contained to make the metal structure finer, the N content is preferably 0.0010% or more, and more preferably 0.0015% or more or 0.0020% or more in order to promote the precipitation of carbonitrides.

[0024] O: 0.0100% or less When O is contained in steel in a large amount, it forms coarse oxides that become the starting point of fracture, causing brittle fracture and hydrogen-induced cracking. Therefore, the O content is set to 0.0100% or less. The O content is preferably 0.0080% or less, more preferably 0.0050% or less or 0.0030% or less. The lower limit of the O content is 0%, but in order to disperse a large number of fine oxides during deoxidation of molten steel, the O content may be set to 0.0005% or more, or 0.0010% or more.

[0025] The hot-rolled steel sheet according to the present embodiment may contain the following elements as optional elements in place of a portion of Fe. When these optional elements are not contained, the lower limit of the content is 0%. The optional elements will be described in detail below.

[0026] Cu: 0.01-2.00% Cr: 0.01~2.00% Mo: 0.01 to 1.00% Ni: 0.01 to 2.00% B: 0.0001 to 0.0100% Cu, Cr, Mo, Ni and B all have the effect of increasing the hardenability of hot-rolled steel sheets. Cu and Mo also have the effect of precipitating in steel as carbides to increase the strength of hot-rolled steel sheets. Furthermore, when Cu is contained, Ni has the effect of effectively suppressing grain boundary cracking of slabs caused by Cu. Therefore, one or more of these elements may be contained.

[0027] As described above, Cu has the effect of increasing the hardenability of hot-rolled steel sheets and the effect of precipitating as carbides in steel at low temperatures to increase the strength of hot-rolled steel sheets. In order to more reliably obtain the effects of the above-mentioned actions, the Cu content is preferably 0.01% or more, and more preferably 0.05% or more. However, if the Cu content exceeds 2.00%, grain boundary cracking of the slab may occur. Therefore, the Cu content is set to 2.00% or less. The Cu content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.

[0028] As described above, Cr has the effect of enhancing the hardenability of hot-rolled steel sheet. In order to obtain the effect of the above action more reliably, the Cr content is preferably 0.01% or more, and more preferably 0.05% or more. However, if the Cr content exceeds 2.00%, the chemical conversion treatability of the hot-rolled steel sheet is significantly reduced. Therefore, the Cr content is set to 2.00% or less. The Cr content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.

[0029] As described above, Mo has the effect of increasing the hardenability of hot-rolled steel sheets and the effect of precipitating in steel as carbides to increase the strength of hot-rolled steel sheets. In order to obtain the above-mentioned effects more reliably, the Mo content is preferably 0.01% or more, and more preferably 0.02% or more. However, even if the Mo content exceeds 1.00%, the above-mentioned effects are saturated and it is not economically preferable. Therefore, the Mo content is set to 1.00% or less. The Mo content is preferably 0.50% or less, more preferably 0.20% or less or 0.10% or less.

[0030] As described above, Ni has the effect of enhancing the hardenability of hot-rolled steel sheet. In addition, when Cu is contained, Ni has the effect of effectively suppressing grain boundary cracking of slabs caused by Cu. In order to obtain the above-mentioned effect more reliably, the Ni content is preferably 0.01% or more. Since Ni is an expensive element, it is economically undesirable to contain a large amount of it. Therefore, the Ni content is set to 2.00% or less. The Ni content is preferably 1.50% or less, more preferably 1.00% or less, 0.70% or less, or 0.50% or less.

[0031] As described above, B has the effect of improving the hardenability of hot-rolled steel sheet. In order to obtain the effect of this action more reliably, the B content is preferably 0.0001% or more, and more preferably 0.0002% or more. However, if the B content exceeds 0.0100%, the formability of the hot-rolled steel sheet is significantly reduced, so the B content is set to 0.0100% or less. The B content is preferably 0.0050% or less or 0.0025% or less.

[0032] Ca: 0.0001 to 0.0200% Mg: 0.0001 to 0.0200% REM: 0.0001 to 0.1000% Bi: 0.0001 to 0.0200% As: 0.001 to 0.100% Ca, Mg and REM all have the effect of adjusting the shape of inclusions in steel to a preferred shape, thereby increasing the ductility of hot-rolled steel sheets. Bi also has the effect of refining the solidification structure, thereby increasing the ductility of hot-rolled steel sheets. Therefore, one or more of these elements may be contained. In order to obtain the effects of the above-mentioned actions more reliably, it is preferable that the content of one or more of Ca, Mg, REM and Bi is 0.0001% or more. However, if the Ca content or Mg content exceeds 0.0200%, or if the REM content exceeds 0.1000%, inclusions are excessively generated in the steel, which may actually reduce the ductility of the hot-rolled steel sheets. Also, even if the Bi content exceeds 0.0200%, the effects of the above-mentioned actions are saturated, which is not economically preferable. Therefore, the Ca content and Mg content are set to 0.0200% or less, the REM content is set to 0.1000% or less, and the Bi content is set to 0.0200% or less. The Ca content, Mg content, and Bi content are preferably 0.0100% or less, more preferably 0.0070% or less or 0.0040% or less. The REM content is preferably 0.0070% or less or 0.0040% or less. As reduces the austenite single-phase temperature, thereby refining prior austenite grains and contributing to improving the ductility of the hot-rolled steel sheet. In order to reliably obtain this effect, it is preferable that the As content is 0.001% or more. On the other hand, even if a large amount of As is contained, the above effect is saturated, so the As content is set to 0.100% or less. Here, REM refers to a total of 17 elements consisting of Sc, Y and lanthanides, and the content of the above REM refers to the total content of these elements. In the case of lanthanides, they are added industrially in the form of misch metals.

[0033] Zr:0.01~1.00%, Co:0.01~1.00%, Zn:0.01~1.00%, W:0.01~1.00% Zr+Co+Zn+W≦1.00% …(B) Each element symbol in the formula (B) indicates the content of the element in mass %, and 0% is substituted when the element is not contained. Sn: 0.01 to 0.05% Concerning Zr, Co, Zn and W, the inventors have confirmed that the effect of the hot-rolled steel sheet according to the present embodiment is not impaired even if these elements are contained in a total of 1.00% or less. Therefore, one or more of Zr, Co, Zn and W may be contained in a total of 1.00% or less. That is, the value of the left side of the formula (B) may be 1.00% or less, 0.50% or less, 0.10% or less, or 0.05% or less. The contents of Zr, Co, Zn, W and Sn may be 0.50% or less, 0.10% or less, or 0.05% or less, respectively. Since Zr, Co, Zn and W do not need to be contained, the contents of each may be 0%. In order to improve the strength of the steel sheet by solid solution strengthening, the contents of Zr, Co, Zn and W may be 0.01% or more, respectively. The inventors have also confirmed that the effect of the hot-rolled steel sheet according to this embodiment is not impaired even if a small amount of Sn is contained. However, if a large amount of Sn is contained, defects may occur during hot rolling, so the Sn content is set to 0.05% or less. Since Sn does not need to be contained, the Sn content may be 0%. In order to improve the corrosion resistance of the hot-rolled steel sheet, the Sn content may be 0.01% or more.

[0034] The balance of the chemical composition of the hot-rolled steel sheet according to the present embodiment may be Fe and impurities. In the present embodiment, the term "impurities" refers to substances mixed in from raw materials such as ore, scrap, or the manufacturing environment, and / or substances that are allowed to have no adverse effect on the hot-rolled steel sheet according to the present embodiment.

[0035] The chemical composition of the above-mentioned hot-rolled steel sheet may be measured by a general analytical method. For example, it may be measured by using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Sol. Al may be measured by ICP-AES using the filtrate after thermally decomposing the sample with acid. C and S may be measured by the combustion-infrared absorption method, N by the inert gas fusion-thermal conductivity method, and O by the inert gas fusion-non-dispersive infrared absorption method. When the hot-rolled steel sheet has a plating layer on the surface, the plating layer may be removed by mechanical grinding or the like, as necessary, before analyzing the chemical composition.

[0036] Metal structure of hot rolled steel sheet Next, the metal structure of the hot-rolled steel sheet according to this embodiment will be described. The hot-rolled steel sheet according to the present embodiment has a metallographic structure in which, in terms of area %, the amount of retained austenite is less than 3.0%, the amount of ferrite is 15.0% or more and less than 60.0%, and the amount of pearlite is less than 5.0%. The entropy value shown in the following formula (1) is 10.7 or more, the inverse differenced normalized value shown in the following formula (2) is 1.020 or more, and the cluster shade value shown in the following formula (3) is −8.0×10 5 ~8.0×10 5 and the standard deviation of the Mn concentration is 0.60 mass % or less.

[0037] Therefore, the hot-rolled steel sheet according to this embodiment has high strength and critical thickness reduction rate at break, while having excellent ductility and shear workability. In this embodiment, the structure fraction, Entropy value, Inverse Differential Normalized value, Cluster Shade value, and standard deviation of Mn concentration in the metal structure at the 1 / 4 depth position of the sheet thickness from the surface (region from 1 / 8 depth of the sheet thickness from the surface to 3 / 8 depth of the sheet thickness from the surface) and at the center position in the sheet width direction in a cross section parallel to the rolling direction are specified. This is because the metal structure at this position shows a typical metal structure of the steel sheet. The surface referred to here means the interface between the plating layer and the steel sheet when the hot-rolled steel sheet has a plating layer.

[0038] Area ratio of retained austenite: less than 3.0% Retained austenite is a metal structure that exists as a face-centered cubic lattice even at room temperature. Retained austenite has the effect of increasing the ductility of hot-rolled steel sheets by transformation-induced plasticity (TRIP). On the other hand, since retained austenite transforms into high-carbon martensite during shear processing, it inhibits stable crack generation and causes the formation of secondary shear planes and a decrease in the critical fracture thickness reduction rate. If the area ratio of retained austenite is 3.0% or more, the above effects become apparent and the shear workability of the hot-rolled steel sheets deteriorates. Therefore, the area ratio of retained austenite is less than 3.0%. The area ratio of retained austenite is preferably less than 1.5%, more preferably less than 1.0%. Since the amount of retained austenite is preferably as small as possible, the area ratio of retained austenite may be 0%.

[0039] Known methods for measuring the area ratio of retained austenite include X-ray diffraction, EBSP (Electron Back Scattering Diffraction Pattern) analysis, magnetic measurement, etc. In this embodiment, the area ratio of retained austenite is measured by X-ray diffraction, which is less susceptible to the effects of polishing (if the effects of polishing are present, the retained austenite may change to other phases such as martensite, making it impossible to measure the true area ratio), and can provide accurate measurement results relatively easily.

[0040] In the measurement of the area ratio of retained austenite by X-ray diffraction in this embodiment, first, in a thickness cross section parallel to the rolling direction at a 1 / 4 depth position (a region from the surface to 1 / 8 depth of the thickness of the plate) and at the center position in the width direction of the plate of the hot rolled steel plate, the integrated intensity of a total of six peaks, α(110), α(200), α(211), γ(111), γ(200), and γ(220), is obtained using Co-Kα radiation, and the volume ratio of retained austenite is calculated using the intensity averaging method. The volume ratio of retained austenite obtained is regarded as the area ratio of retained austenite.

[0041] Ferrite area ratio: 15.0% or more, less than 60.0% Ferrite is a structure that is formed when fcc transforms to bcc at a relatively high temperature. Ferrite has a high work hardening rate, and therefore has the effect of improving the strength-ductility balance of hot-rolled steel sheets. To obtain the above effect, the area ratio of ferrite is set to 15.0% or more. It is preferably 20.0% or more, more preferably 25.0% or more, and even more preferably 30.0% or more. On the other hand, since ferrite has low strength, if the area ratio is excessive, the desired strength cannot be obtained. Therefore, the ferrite area ratio is set to less than 60.0%, preferably 50.0% or less, and more preferably 45.0% or less or 40.0% or less.

[0042] Percentage of pearlite: less than 5.0% Pearlite is a lamellar metal structure in which cementite is precipitated in layers between ferrite, and is softer than bainite and martensite. If the area ratio of pearlite is 5.0% or more, carbon is consumed by the cementite contained in pearlite, and the strength of the remaining structure, martensite and bainite, decreases, making it impossible to obtain the desired strength. Therefore, the area ratio of pearlite is set to less than 5.0%. The area ratio of pearlite is preferably 3.0% or less, 2.0% or less, or 1.0% or less. In order to improve the stretch flangeability of the hot-rolled steel sheet, it is preferable to reduce the area ratio of pearlite as much as possible, and it is even more preferable that the area ratio of pearlite is 0%.

[0043] In addition, the hot-rolled steel sheet according to the present embodiment includes a hard structure consisting of one or more of bainite, martensite, and tempered martensite, the total area ratio of which is more than 32.0% and not more than 85.0%, as a remaining structure other than the retained austenite, ferrite, and pearlite. The lower limit of these remaining structures may be 36.0%, 40.0%, 44.0%, 48.0%, 52.0%, or 55.0%, and the upper limit may be 82.0%, 78.0%, 74.0%, 70.0%, or 66.0%. The remaining structure other than the retained austenite, ferrite, and pearlite may be one or more of bainite, martensite, and tempered martensite.

[0044] The area ratio of the metal structure is measured by the following method. A thickness cross section parallel to the rolling direction is mirror-finished and polished for 8 minutes at room temperature using colloidal silica that does not contain an alkaline solution to remove strain introduced into the surface layer of the sample. At any position in the longitudinal direction of the sample cross section, a length of 50 μm, a position at a depth of 1 / 4 of the plate thickness from the surface (a region from a depth of 1 / 8 of the plate thickness from the surface to a depth of 3 / 8 of the plate thickness from the surface), and a region at the center position in the plate width direction are measured by electron backscatter diffraction at measurement intervals of 0.1 μm to obtain crystal orientation information. For the measurement, an EBSD analysis device consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSD detector (TSL DVC5 type detector) is used. At this time, the degree of vacuum inside the EBSD analysis device is 9.6 × 10 -5 The conditions are: 1. the luminance is 1.0 Pa or less, 2. the acceleration voltage is 15 kV, the probe current level is 13, and the electron beam irradiation level is 62. The observation area is 40,000 μm 2 Let us assume that.

[0045] Furthermore, a backscattered electron image is taken in the same field of view. First, the crystal grains in which ferrite and cementite are precipitated in layers are identified from the backscattered electron image, and the area ratio of the crystal grains is calculated to obtain the area ratio of pearlite. Then, for the crystal grains determined to have a body-centered cubic lattice structure among the crystal grains excluding the crystal grains determined to be pearlite, the obtained crystal orientation information is used to determine the region with a Grain Average Misorientation value of 1.0° or less as ferrite using the "Grain Average Misorientation" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device. At this time, the Grain Tolerance Angle is set to 15°, and the area ratio of the region determined to be ferrite is obtained to obtain the area ratio of the ferrite.

[0046] Next, the area ratio of the regions excluding the regions determined to be pearlite or ferrite is measured, and this is taken as the area ratio of the remaining structure (i.e., bainite, martensite, and tempered martensite). If it is desired to measure the area ratio of bainite and the sum of the area ratios of martensite and tempered martensite, these area ratios can be measured by the following method. Specifically, when the maximum value of the "Grain Average IQ" of the ferrite region with respect to the remaining region is Iα, the region exceeding Iα / 2 is extracted (determined) as bainite, and the region equal to or less than Iα / 2 is extracted (determined) as "martensite or tempered martensite". The area ratio of bainite is obtained by calculating the area ratio of the region extracted (determined) as bainite. In addition, the area ratio of the region extracted (determined) as martensite or tempered martensite is calculated, and the sum of the area ratios of martensite and tempered martensite is obtained.

[0047] In this embodiment, the area ratio of each structure is measured by X-ray diffraction and EBSD analysis, so the total of the area ratios of each structure obtained by measurement may not be 100.0%. If the total of the area ratios of each structure obtained by the above-mentioned method is not 100.0%, the area ratios of each structure are converted so that the total of the area ratios of each structure becomes 100.0%. For example, if the total of the area ratios of each structure is 103.0%, the area ratios of each structure are multiplied by "100.0 / 103.0" to obtain the area ratio of each structure.

[0048] Entropy value: 10.7 or more, Inverse differenced normalized value: 1.020 or more In order to suppress the generation of secondary shear planes, it is important to form fracture surfaces after sufficient shear planes have been formed, and it is necessary to suppress early generation of cracks from the cutting edge of the tool during shear processing. For this purpose, it is important that the periodicity of the metal structure is low and the uniformity of the metal structure is high. In this embodiment, the generation of secondary shear planes is suppressed by controlling the entropy value (E value), which indicates the periodicity of the metal structure, and the inverse differenced normalized value (I value), which indicates the uniformity of the metal structure.

[0049] The E value represents the periodicity of the metal structure. When the luminance is arranged periodically due to the effect of the formation of a band-shaped structure, that is, when the periodicity of the metal structure is high, the E value decreases. In this embodiment, it is necessary to make the metal structure have a low periodicity, so it is necessary to increase the E value. If the E value is less than 10.7, a secondary shear surface is likely to be generated. Starting from the periodically arranged structure, a crack is generated from the cutting edge of the shear tool at a very early stage of the shear processing, forming a fracture surface, and then a shear surface is formed again. This is estimated to make it easier for a secondary shear surface to be generated. Therefore, the E value is set to 10.7 or more. It is preferably 10.8 or more, and more preferably 11.0 or more. The higher the E value, the better. There is no particular upper limit to the E value, but it may be 13.0 or less, 12.5 or less, or 12.0 or less.

[0050] The I value represents the uniformity of the metal structure, and increases as the area of ​​the region having a certain brightness becomes larger. A high I value means that the metal structure is highly uniform. In the hot-rolled steel sheet having a metal structure with an area ratio of ferrite of 15.0% or more and less than 60.0%, which is the present embodiment, it is necessary to make the metal structure highly uniform. For this reason, in the present embodiment, it is necessary to increase the I value. If the I value is less than 1.020, due to the influence of the hardness distribution caused by the precipitates in the crystal grains and the element concentration difference, a crack occurs from the cutting edge of the shearing tool at a very early stage of the shearing process, forming a fracture surface, and then a shear surface is formed again. This is estimated to make it easier for a secondary shear surface to occur. Therefore, the I value is set to 1.020 or more. It is preferably 1.025 or more, and more preferably 1.030 or more. The higher the I value, the better. There is no particular upper limit to the I value, but it may be 1.200 or less, 1.150 or less, or 1.100 or less.

[0051] Cluster Shade value: -8.0×10 5 ~8.0×10 5 The Cluster Shade (CS) value indicates the degree of distortion of the metal structure. The CS value is positive when there are many points with brightness above the average brightness in the image obtained by photographing the metal structure, and negative when there are many points with brightness below the average brightness.

[0052] In the secondary electron image of a scanning electron microscope, the brightness is high where the surface unevenness of the observed object is large, and the brightness is low where the unevenness is small. The unevenness of the surface of the observed object is greatly affected by the grain size and strength distribution in the metal structure. In this embodiment, the CS value is high when the strength variation of the metal structure is large or the structure unit is small, and is low when the strength variation is small or the structure unit is large.

[0053] In this embodiment, it is important to keep the CS value in a desired range close to 0. 5If the CS value is less than -8.0×10, the critical thickness reduction rate of the hot-rolled steel sheet decreases. This is presumably because large grains exist in the metal structure and these grains are preferentially fractured during extreme deformation. Therefore, the CS value is -8.0×10 5 More than or equal to -7.5×10 5 More preferably, it is −7.0×10 5 That's all. On the other hand, the CS value is 8.0 × 10 5 When the CS value is more than 8.0×10, the critical thickness reduction rate of the hot-rolled steel sheet at fracture decreases. This is presumably because the microscopic strength variation in the metal structure is large, and the strain during the ultimate deformation is concentrated locally, making the steel sheet more likely to fracture. Therefore, the CS value is 8.0×10 5 The value should be less than 7.5×10 5 More preferably, it is 7.0×10 or less. 5 The following is the result.

[0054] The E value, I value and CS value can be obtained by the following method. In this embodiment, the photographed region of the SEM image (secondary electron image of a scanning electron microscope) taken to calculate the E value, I value, and CS value is a position at a 1 / 4 depth of the plate thickness from the surface (a region from 1 / 8 depth of the plate thickness from the surface to 3 / 8 depth of the plate thickness from the surface) in the plate thickness cross section parallel to the rolling direction, and at the center position in the plate width direction. A Hitachi High-Technologies Corporation SU-6600 Schottky electron gun is used to take the SEM image, with a tungsten emitter and an acceleration voltage of 1.5 kV. With the above settings, the SEM image is output at a magnification of 1000 times and a gray scale of 256 gradations.

[0055] Next, the obtained SEM image is cut into an 880 x 880 pixel region (observation region is 160 μm x 160 μm in actual size) and the image is subjected to smoothing processing with a tile grid size of 8 x 8 and a contrast enhancement limiting factor of 2.0 as described in Non-Patent Document 3. The smoothed SEM image is rotated counterclockwise in 1 degree increments from 0 to 179 degrees, excluding 90 degrees, and an image is created for each degree, resulting in a total of 179 images. Next, for each of these 179 images, the GLCM method described in Non-Patent Document 1 is used to collect the frequency values ​​of luminance between adjacent pixels in the form of a matrix.

[0056] The matrix of 179 frequency values ​​collected by the above method is expressed as p k (k=0 89, 91, 179). For each image, the generated p k is summed for all k (k=0...89, 91...179), and then a 256 × 256 matrix P is calculated in which the sum of each component is normalized to 1. Furthermore, the E value, I value, and CS value are calculated using the following formulas (1) to (5) described in Non-Patent Document 2. In the following formulas (1) to (5), P(i,j) is a gray level co-occurrence matrix, and the value in the i-th row and j-th column of the matrix P is expressed as P(i,j). As described above, the calculation is performed using a 256 x 256 matrix P, so if you want to emphasize this point, you can modify the following formulas (1) to (5) to the following formulas (1') to (5'). Here, L in the following formula (2) is the number of quantization levels of grayscale that an SEM image can have, and in this embodiment, since an SEM image is output in a grayscale of 256 levels as described above, L is 256. In the following formulas (2) and (3), i and j are natural numbers from 1 to L, and μ in the following formula (3) is x and μ y are expressed by the following equations (4) and (5), respectively. In the following formulas (1') to (5'), the value in the i-th row and j-th column of the matrix P is P ij It is written as follows.

[0057]

number

[0058]

number

[0059]

number

[0060]

number

[0061]

number

[0062]

number

[0063]

number

[0064]

number

[0065]

number

[0066]

number

[0067] Standard deviation of Mn concentration: 0.60 mass% or less The standard deviation of the Mn concentration at the 1 / 4 depth position of the plate thickness from the surface of the hot rolled steel plate according to this embodiment (the region from 1 / 8 depth of the plate thickness from the surface to 3 / 8 depth of the plate thickness from the surface) and at the center position in the plate width direction is 0.60 mass% or less. This allows the hard phase to be uniformly dispersed, and it is possible to prevent cracks from occurring from the cutting edge of the shearing tool at a very early stage of shearing. As a result, it is possible to suppress the occurrence of secondary shear planes. The standard deviation of the Mn concentration is preferably 0.55 mass% or less or 0.50 mass% or less, and more preferably 0.47 mass% or less or 0.45 mass% or less. From the viewpoint of suppressing excessive burrs, the smaller the lower limit of the standard deviation of the Mn concentration, the more desirable it is, but due to the constraints of the manufacturing process, the substantial lower limit is 0.10 mass%. If necessary, the lower limit may be 0.20 mass% or 0.28 mass%.

[0068] After mirror polishing the cross section of the hot-rolled steel sheet parallel to the rolling direction, the standard deviation of the Mn concentration is measured at a 1 / 4 depth position of the sheet thickness from the surface (a region from 1 / 8 depth of the sheet thickness from the surface to 3 / 8 depth of the sheet thickness from the surface) and at the center position in the sheet width direction with an electron probe microanalyzer (EPMA). The measurement conditions are an acceleration voltage of 15 kV and a magnification of 5000 times, and a distribution image is measured in a range of 20 μm in the rolling direction of the sample and 20 μm in the thickness direction of the sample. More specifically, the measurement interval is 0.1 μm, and the Mn concentration is measured at 40,000 or more points. Next, the standard deviation is calculated based on the Mn concentrations obtained from all the measurement points to obtain the standard deviation of the Mn concentration.

[0069] Average crystal grain size of surface layer: less than 3.0 μm By making the crystal grain size of the surface fine, it is possible to suppress cracks on the inside of the bend of hot-rolled steel sheets. The higher the strength of hot-rolled steel sheets, the more likely they are to crack from the inside of the bend during bending (hereinafter referred to as cracks on the inside of the bend). The mechanism of cracks on the inside of the bend is presumed to be as follows. During bending, compressive stress is generated on the inside of the bend. At first, the entire inside of the bend is uniformly deformed as the processing progresses, but as the amount of processing increases, the uniform deformation alone is no longer able to support the deformation, and strain is concentrated locally, causing the deformation to progress (generation of shear deformation bands). As this shear deformation band continues to grow, cracks are generated along the shear bands from the inside surface of the bend and grow. It is presumed that the reason why cracks on the inside of the bend are more likely to occur with increasing strength is that the decrease in work hardening ability associated with increasing strength makes it difficult for uniform deformation to proceed, making it easier for deformation bias to occur, which causes shear deformation bands to occur early in processing (or under loose processing conditions).

[0070] The inventors' research has revealed that bending cracks become prominent in steel sheets with a tensile strength of 980 MPa or more. The inventors have also found that the finer the crystal grain size of the surface layer of the hot-rolled steel sheet, the more local strain concentration is suppressed, and bending cracks are less likely to occur. In order to obtain the above effect, it is preferable that the average crystal grain size of the surface layer of the hot-rolled steel sheet is less than 3.0 μm. Therefore, in this embodiment, the average crystal grain size of the surface layer may be less than 3.0 μm. The average crystal grain size of the surface layer is more preferably 2.7 μm or less or 2.5 μm or less. The lower limit of the average crystal grain size of the surface layer region is not particularly specified, but may be 0.5 μm or 1.0 μm. In this embodiment, the surface layer refers to a region from the surface of the hot-rolled steel sheet to a depth of 50 μm from the surface. As described above, the surface here refers to the interface between the plating layer and the steel sheet when the hot-rolled steel sheet has a plating layer.

[0071] The crystal grain size of the surface layer is measured using EBSP-OIM (Electron Back Scatter Diffraction Pattern-Orientation Image Microscopy) method. EBSP-OIM method is performed using a device that combines a scanning electron microscope and an EBSP analysis device and OIM Analysis (registered trademark) manufactured by AMETEK. The analyzable area of ​​EBSP-OIM method is the area that can be observed by SEM. Although it depends on the resolution of SEM, EBSP-OIM method can analyze with a minimum resolution of 20 nm.

[0072] In a cross section of the hot-rolled steel sheet parallel to the rolling direction, an analysis is performed in at least five fields of view in a region of 40 μm × 30 μm at a magnification of 1200 times in a region from the surface of the hot-rolled steel sheet to a depth of 50 μm from the surface and at the center position in the sheet width direction. A location where the angle difference between adjacent measurement points is 5° or more is defined as a grain boundary, and the area-average grain size is calculated. The obtained area-average grain size is regarded as the average grain size of the surface layer.

[0073] Note that retained austenite is not a structure formed by phase transformation at 600°C or below, and does not have the effect of dislocation accumulation, so it is not included in the analysis in this measurement method (a method for measuring the average crystal grain size of the surface layer). When the area ratio of retained austenite is 0%, it does not need to be excluded from the analysis, but in cases where there is a possibility that it may affect the measurement of the average crystal grain size of the surface layer, the EBSP-OIM method measures retained austenite, which has an fcc crystal structure, by excluding it from the analysis.

[0074] Tensile strength properties Among the mechanical properties of hot-rolled steel sheets, the tensile strength characteristics (tensile strength, total elongation) are evaluated in accordance with JIS Z 2241:2011. The test piece used is No. 5 test piece of JIS Z 2241:2011. The tensile test piece is taken from the 1 / 4 part from the end in the sheet width direction, and the direction perpendicular to the rolling direction is the longitudinal direction.

[0075] The hot-rolled steel sheet according to the present embodiment has a tensile strength (TS) of 980 MPa or more. It is preferably 1000 MPa or more. If the tensile strength is less than 980 MPa, the applicable parts are limited, and the contribution to the weight reduction of the vehicle body is small. There is no need to set the upper limit in particular, but it may be set to 1780 MPa from the viewpoint of suppressing die wear.

[0076] In addition, the total elongation of the hot-rolled steel sheet according to this embodiment is preferably 10.0% or more, and the product of the tensile strength and the total elongation (TS×El) is preferably 13000MPa·% or more. The total elongation is more preferably 11.0% or more, and even more preferably 13.0% or more. The product of the tensile strength and the total elongation is more preferably 14000MPa·% or more, and even more preferably 15000MPa·%MPa or more. By making the total elongation 10.0% or more and the product of the tensile strength and the total elongation 13000MPa·% or more, it is possible to greatly contribute to reducing the weight of the vehicle body without limiting the applicable parts. There is no need to set an upper limit for the product of the tensile strength and the total elongation, but it may be 22000MPa·% or 18000MPa·%. There is no need to set an upper limit for the total elongation, but it may be 30.0%, 25.0%, or 22.0%.

[0077] Plate thickness The thickness of the hot rolled steel sheet according to the present embodiment is not particularly limited, but may be 0.5 to 8.0 mm. If the thickness of the hot rolled steel sheet is less than 0.5 mm, it may be difficult to ensure the rolling completion temperature and the rolling load may become excessive, making hot rolling difficult. Therefore, the thickness of the hot rolled steel sheet according to the present embodiment may be 0.5 mm or more. It is preferably 1.2 mm or more, 1.4 mm or more, or 1.8 mm or more. On the other hand, if the thickness exceeds 8.0 mm, it may be difficult to refine the metal structure, and it may be difficult to obtain the above-mentioned metal structure. Therefore, the thickness may be 8.0 mm or less. It is preferably 6.0 mm or less, 5.0 mm or less, or 4.0 mm or less.

[0078] Plating layer The hot-rolled steel sheet according to the present embodiment having the above-mentioned chemical composition and metal structure may be provided with a plating layer on the surface for the purpose of improving corrosion resistance, etc., to form a surface-treated steel sheet. The plating layer may be an electroplating layer or a hot-dip plating layer. Examples of the electroplating layer include electrogalvanizing and electrolytic Zn-Ni alloy plating. Examples of the hot-dip plating layer include hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip aluminum plating, hot-dip Zn-Al alloy plating, hot-dip Zn-Al-Mg alloy plating, and hot-dip Zn-Al-Mg-Si alloy plating. The coating weight is not particularly limited and may be the same as that of the conventional method. In addition, it is also possible to further improve the corrosion resistance by performing an appropriate chemical conversion treatment (for example, application of a silicate-based chromium-free chemical conversion treatment solution and drying) after plating.

[0079] Manufacturing conditions A suitable method for producing the hot-rolled steel sheet according to this embodiment having the above-mentioned chemical composition and metal structure is as follows.

[0080] In a preferred method for producing a hot-rolled steel sheet according to this embodiment, the following steps (1) to (10) are sequentially performed. Note that the temperature of the slab and the temperature of the steel sheet in this embodiment refer to the surface temperature of the slab and the surface temperature of the steel sheet. Also, the stress refers to the tension applied in the rolling direction of the steel sheet.

[0081] (1) The slab is held in the temperature range of 700 to 850°C for 900 seconds or more, and then further heated and held in the temperature range of 1100°C or higher for 6000 seconds or more. (2) Hot rolling is performed in the temperature range of 850 to 1100°C to reduce the plate thickness by a total of 90% or more. (3) After the rolling stage before the final stage of hot rolling and before the final stage of rolling, a stress of 170 kPa or more is applied to the steel plate. (4) The reduction rate in the final stage of hot rolling is 8% or more, and the hot rolling is completed so that the rolling completion temperature Tf is 900°C or more and less than 1010°C. (5) The stress applied to the steel plate after the final stage of hot rolling and before the steel plate is cooled to 800°C is less than 200 kPa. (6) Cool to a temperature range of the hot rolling completion temperature Tf-50°C or lower within 1 second after the completion of hot rolling, and then accelerate cool to a temperature range of 600 to 730°C at an average cooling rate of 50°C / s or higher. However, cooling to a temperature range of the hot rolling completion temperature Tf-50°C or lower within 1 second after the completion of hot rolling is a more preferable cooling condition. (7) Slow cooling is performed for 2.0 seconds or more in a temperature range of 600 to 730°C with an average cooling rate of less than 5°C / s. (8) After completion of the slow cooling, the material is cooled so that the average cooling rate in the temperature range of 450 to 600°C is 30°C / s or more and less than 50°C / s. (9) Cooling is performed so that the average cooling rate in the temperature range from the coiling temperature to 450°C is 50°C / s or more. (10) Coiling is performed at a temperature of 350°C or less.

[0082] By adopting the above-mentioned manufacturing method, it is possible to stably manufacture a hot-rolled steel sheet having a metal structure with high strength, a critical sheet thickness reduction rate at fracture, excellent ductility, and excellent shear workability. That is, by appropriately controlling the slab heating conditions and the hot rolling conditions, Mn segregation is reduced and the pre-transformation austenite is made equiaxed, and in combination with the cooling conditions after hot rolling described later, it is possible to stably manufacture a hot-rolled steel sheet having a desired metal structure.

[0083] (1) Slab, slab temperature and holding time when subjected to hot rolling The slab to be subjected to hot rolling may be a slab obtained by continuous casting or a slab obtained by casting and blooming. If necessary, the slab may be subjected to hot working or cold working.

[0084] The slab to be subjected to hot rolling is preferably held in a temperature range of 700 to 850°C for 900 seconds or more during slab heating, and then further heated and held in a temperature range of 1100°C or higher for 6000 seconds or more. When held in a temperature range of 700 to 850°C, the steel sheet temperature may be varied within this temperature range or may be constant. When held in a temperature range of 1100°C or higher, the steel sheet temperature may be varied within a temperature range of 1100°C or higher or may be constant.

[0085] In the austenite transformation in the temperature range of 700 to 850°C, Mn is distributed between ferrite and austenite, and by extending the transformation time, Mn can diffuse into the ferrite region. This eliminates Mn microsegregation unevenly distributed in the slab, and significantly reduces the standard deviation of the Mn concentration. In addition, by holding the slab at a temperature range of 1100°C or higher for 6000 seconds or more, the austenite grains can be made uniform during slab heating.

[0086] In the hot rolling, a reverse mill or a tandem mill is preferably used as a multi-pass rolling mill. In particular, from the viewpoint of industrial productivity and the stress load on the steel sheet during rolling, it is more preferable to use a tandem mill for at least the final two stages of hot rolling.

[0087] (2) Reduction rate of hot rolling: Total thickness reduction of 90% or more in the temperature range of 850 to 1100°C By performing hot rolling so as to reduce the sheet thickness by 90% or more in total in the temperature range of 850 to 1100°C, mainly recrystallized austenite grains are refined and the accumulation of strain energy in the unrecrystallized austenite grains is promoted. In addition, the recrystallization of austenite is promoted and the atomic diffusion of Mn is promoted, so that the standard deviation of the Mn concentration can be reduced. Therefore, it is preferable to perform hot rolling so as to reduce the sheet thickness by 90% or more in total in the temperature range of 850 to 1100°C.

[0088] The thickness reduction in the temperature range of 850 to 1100°C can be expressed as {(t0-t1) / t0}×100(%), where t0 is the entrance thickness before the first rolling in this temperature range and t1 is the exit thickness after the final rolling stage in this temperature range.

[0089] (3) Stress after the rolling stage before the final stage of hot rolling and before the final stage of rolling: 170 kPa or more It is preferable that the stress applied to the steel sheet after the rolling one stage before the final stage of hot rolling and before the final stage of rolling is 170 kPa or more. <001> The number of grains having a crystal orientation of {110} can be reduced. <001> Since this crystal orientation is difficult to recrystallize, suppressing the formation of this crystal orientation effectively promotes recrystallization during the final reduction stage. As a result, the band-shaped structure of the hot-rolled steel sheet is improved, the periodicity of the metal structure is reduced, and the E value is increased.

[0090] If the stress applied to the steel sheet is less than 170 kPa, it may not be possible to obtain a desired E value. The stress applied to the steel sheet is more preferably 190 kPa or more. The stress applied to the steel plate can be controlled by adjusting the roll rotation speed during tandem rolling, and can be determined by dividing the load in the rolling direction measured in the rolling stand by the cross-sectional area of ​​the plate being passed through.

[0091] (4) Reduction rate in the final stage of hot rolling: 8% or more, hot rolling completion temperature Tf: 900°C or more, less than 1010°C It is preferable that the reduction rate in the final stage of hot rolling is 8% or more, and the hot rolling completion temperature Tf is 900°C or more. By setting the reduction rate in the final stage of hot rolling to 8% or more, recrystallization due to the reduction in the final stage can be promoted. As a result, the band-shaped structure of the hot rolled steel sheet is improved, the periodicity of the metal structure is reduced, and the E value is increased. By setting the hot rolling completion temperature Tf to 900°C or more, an excessive increase in the number of ferrite nucleation sites in austenite can be suppressed. As a result, the generation of ferrite in the final structure (metal structure of the hot rolled steel sheet after production) can be suppressed, and a high-strength hot rolled steel sheet can be obtained. In addition, by setting the hot rolling completion temperature Tf to less than 1010°C, the coarsening of the austenite grain size can be suppressed, the periodicity of the metal structure can be reduced, and the E value can be set to a desired value.

[0092] (5) Stress after the final stage of hot rolling and until the steel plate is cooled to 800°C: Less than 200 kPa The stress applied to the steel sheet after the final stage of hot rolling and before the steel sheet is cooled to 800°C is preferably less than 200 kPa. By setting the stress (tension) applied in the rolling direction of the steel sheet to less than 200 kPa, austenite recrystallization preferentially proceeds in the rolling direction, and an increase in the periodicity of the metal structure can be suppressed. As a result, the E value can be set to a desired value. The stress applied to the steel sheet is more preferably 180 MPa or less. The stress applied in the rolling direction of the steel sheet can be controlled by adjusting the rotation speed of the rolling stand and the winding device, and can be obtained by dividing the measured load in the rolling direction by the cross-sectional area of ​​the sheet being passed through.

[0093] (6) Within 1 second after the completion of hot rolling, the material is cooled to a temperature range below the hot rolling completion temperature Tf-50°C, and then accelerated cooling is performed at an average cooling rate of 50°C / s or more to a temperature range of 600 to 730°C. In order to suppress the growth of austenite grains refined by hot rolling, it is more preferable to cool the steel sheet by 50°C or more within 1 second after the completion of hot rolling. In order to cool the steel sheet to a temperature range of the hot rolling completion temperature Tf-50°C or less within 1 second after the completion of hot rolling, cooling with a high average cooling rate may be performed immediately after the completion of hot rolling, for example, by spraying cooling water on the steel sheet surface. By cooling the steel sheet to a temperature range of Tf-50°C or less within 1 second after the completion of hot rolling, the grain size of the surface layer can be refined, and the resistance to internal bending cracking of the hot rolled steel sheet can be improved.

[0094] In addition, by performing accelerated cooling to a temperature range of 730°C or less at an average cooling rate of 50°C / s or more after the above cooling, it is possible to suppress the formation of ferrite and pearlite, which have a small amount of precipitation strengthening. This improves the strength of the hot-rolled steel sheet. The average cooling rate here refers to the value obtained by dividing the temperature drop of the steel sheet from the start of accelerated cooling (when the steel sheet is introduced into the cooling equipment) to the end of accelerated cooling (when the steel sheet is removed from the cooling equipment) by the time required from the start of accelerated cooling to the end of accelerated cooling.

[0095] Although the upper limit of the cooling rate is not particularly specified, a faster cooling rate requires larger cooling equipment and higher equipment costs. Therefore, in consideration of equipment costs, a cooling rate of 300°C / s or less is preferable. In addition, the cooling stop temperature of the accelerated cooling is preferably 600°C or higher in order to perform slow cooling, which will be described later.

[0096] (7) In the temperature range of 600 to 730°C, slow cooling is performed with an average cooling rate of less than 5°C / s for 2.0 seconds or more. By performing slow cooling at an average cooling rate of less than 5°C / s for 2.0 seconds or more in the temperature range of 600 to 730°C, precipitation-strengthened ferrite can be sufficiently precipitated, thereby achieving both strength and ductility of the hot-rolled steel sheet. The average cooling rate referred to here means the value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of accelerated cooling to the stop temperature of slow cooling by the time required from the stop of accelerated cooling to the stop of slow cooling.

[0097] The time for slow cooling is preferably 3.0 seconds or more. The upper limit of the time for slow cooling is determined by the equipment layout, but it is generally sufficient to set it to less than 10.0 seconds. There is no particular lower limit for the average cooling rate of slow cooling, but since raising the temperature without cooling requires a large investment in equipment, it may be set to 0°C / s or more.

[0098] (8) After the slow cooling is completed, the temperature range of 450 to 600°C is cooled so that the average cooling rate is 30°C / s or more and less than 50°C / s. After the slow cooling is completed, it is preferable to cool the material so that the average cooling rate in the temperature range of 450 to 600°C is 30°C / s or more and less than 50°C / s. By setting the average cooling rate in the temperature range to 30°C / s or more and less than 50°C / s, the CS value can be set to a desired value. If the average cooling rate exceeds 50°C / s, a flat lath-like structure with low brightness is likely to be generated, and the CS value is -8.0×10 5 When the average cooling rate is less than 30°C / s, the concentration of carbon in the untransformed portion is promoted, the strength of the hard structure increases, and the strength difference with the soft structure increases, so the CS value is less than 8.0×10 5 Become super. The average cooling rate referred to here means the value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of slow cooling with an average cooling rate of less than 5°C / s to the cooling stop temperature of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s, by the time required from the stop of slow cooling with an average cooling rate of less than 5°C / s to the stop of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s.

[0099] (9) Average cooling rate in the temperature range from coiling temperature to 450°C: 50°C / s or more In order to suppress the area ratio of pearlite and retained austenite and obtain the desired strength and formability, it is preferable to set the average cooling rate in the temperature range from the coiling temperature to 450° C. to 50° C. / s or more, which makes it possible to harden the matrix structure. The average cooling rate referred to here means a value obtained by dividing the temperature drop of the steel sheet from the cooling stop temperature to the coiling temperature in the case where the average cooling rate is 30°C / s or more and less than 50°C / s, by the time required from the stop of cooling to coiling in the case where the average cooling rate is 30°C / s or more and less than 50°C / s.

[0100] (10) Winding temperature: 350°C or less The coiling temperature is set to 350°C or less. By setting the coiling temperature to 350°C or less, the amount of iron carbide precipitated can be reduced, and the variation in hardness distribution within the hard phase can be reduced. As a result, the I value can be increased, and the occurrence of secondary shear planes can be suppressed. EXAMPLES

[0101] Next, the effect of one embodiment of the present invention will be described in more detail with reference to an example, but the conditions in the example are merely an example of conditions adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this example of conditions. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and the object of the present invention is achieved.

[0102] Steels having the chemical compositions shown in Tables 1 and 2 were melted and continuously cast into slabs with thicknesses of 240 to 300 mm. The resulting slabs were used to obtain hot-rolled steel sheets shown in Tables 5 and 6 under the manufacturing conditions shown in Tables 3 and 4. The average cooling rate of the slow cooling was less than 5°C / s. In addition, since the coiling temperature shown in Table 4 has a lower measurement limit of 50°C, the actual coiling temperature in the examples shown as 50°C is 50°C or lower.

[0103] The area ratio of the metal structure, E value, I value, CS value, standard deviation of Mn concentration, average crystal grain size of the surface layer, tensile strength TS, and total elongation El of the obtained hot-rolled steel sheets were measured by the above-mentioned methods. The measurement results are shown in Tables 5 and 6. The remaining structure was one or more of bainite, martensite, and tempered martensite.

[0104] Method for evaluating the properties of hot-rolled steel sheets Tensile properties If the tensile strength (TS) was 980MPa or more, the total elongation (El) was 10.0% or more, and the tensile strength (TS) × total elongation (El) was 13,000MPa·% or more, the hot-rolled steel sheet was deemed to have high strength and excellent ductility and passed the test. If any one of the conditions was not met, the hot-rolled steel sheet was deemed to have neither high strength nor excellent ductility and failed the test.

[0105] Limiting thickness reduction rate at break The critical thickness reduction rate at break of the hot-rolled steel sheets was evaluated by a tensile test. The tensile test was carried out in the same manner as when the tensile properties were evaluated. The thickness before the tensile test was t1, and the minimum thickness at the center of the width direction of the tensile test piece after fracture was t2. The limiting fracture thickness reduction rate was obtained by calculating the value of (t1-t2) x 100 / t1. The tensile test was carried out five times, and the limiting fracture thickness reduction rate was obtained by calculating the average value of the three times excluding the maximum and minimum values ​​of the limiting fracture thickness reduction rate.

[0106] When the critical fracture thickness reduction rate was 60.0% or more, the hot-rolled steel sheet was judged to have a high critical fracture thickness reduction rate and to have passed the test. On the other hand, when the critical fracture thickness reduction rate was less than 60.0%, the hot-rolled steel sheet was judged to have a high critical fracture thickness reduction rate and to have failed the test.

[0107] Shear workability (secondary shear surface evaluation) The shear workability of the hot-rolled steel sheets was evaluated by a punching test. Three punched holes were made for each example with a hole diameter of 10 mm, a clearance of 10%, and a punching speed of 3 m / s. Next, the cross section perpendicular to the rolling direction of the punched holes and the cross section parallel to the rolling direction were embedded in resin, and the cross-sectional shape was photographed with a scanning electron microscope. In the obtained observation photograph, the sheared end surface as shown in FIG. 1 or FIG. 2 can be observed. Note that FIG. 1 is an example of the sheared end surface of a hot-rolled steel sheet according to an example of the present invention, and FIG. 2 is an example of the sheared end surface of a hot-rolled steel sheet according to a comparative example. In FIG. 1, the sheared end surface is sag-sheared surface-fracture surface-burr. On the other hand, in FIG. 2, the sheared end surface is sag-sheared surface-fracture surface-sheared surface-fracture surface-burr. Here, sagging refers to the smooth R-shaped surface area, the shear surface refers to the area of ​​the punched end surface that is separated by shear deformation, the fracture surface refers to the area of ​​the punched end surface that is separated by a crack that has initiated near the cutting edge, and the burr refers to a surface with a protrusion protruding from the underside of the hot-rolled steel sheet.

[0108] Among the obtained sheared end surfaces, if a shear surface-fracture surface-shear surface, as shown in Figure 2, was observed on two surfaces perpendicular to the rolling direction and two surfaces parallel to the rolling direction, it was determined that a secondary shear surface had been formed. Four surfaces for each punched hole, for a total of 12 surfaces, were observed, and if none of the surfaces showed a secondary shear surface, the hot-rolled steel sheet was deemed to have excellent shear workability and passed the test, and this was recorded as "absent" in the table. On the other hand, if even one secondary shear surface was formed, the hot-rolled steel sheet was deemed to not have excellent shear workability and failed the test, and this was recorded as "present" in the table.

[0109] Resistance to internal cracking when bent The resistance to internal cracking due to bending was evaluated by the following bending test. A 100mm x 30mm rectangular test piece was cut from the 1 / 2 position in the width direction of the hot-rolled steel sheet to obtain a bending test piece. Tests were conducted in accordance with the V-block method (bending angle θ is 90°) of JIS Z 2248:2006 for both bending in which the bending ridgeline is parallel to the rolling direction (L direction) (L-axis bending) and bending in which the bending ridgeline is parallel to the direction perpendicular to the rolling direction (C direction) (C-axis bending). From this, the minimum bending radius at which cracks do not occur was obtained, and the resistance to internal bending cracking was investigated. The value obtained by dividing the average value of the minimum bending radii in the L axis and C axis by the sheet thickness was used as the limit bending R / t, which was used as an index value of resistance to internal bending cracking. If R / t was 2.5 or less, it was determined that the hot-rolled steel sheet had excellent resistance to internal bending cracking.

[0110] However, to determine the presence or absence of cracks, the cross section of the test piece after the test was cut parallel to the bending direction and perpendicular to the plate surface, mirror-polished, and then observed for cracks under an optical microscope. If the length of the crack observed on the inside of the bent test piece exceeded 30 μm, it was determined that a crack was present.

[0111] [Table 1]

[0112] [Table 2]

[0113] [Table 3]

[0114] [Table 4]

[0115] [Table 5]

[0116] [Table 6]

[0117] From Tables 5 and 6, it can be seen that the hot-rolled steel sheets according to the examples of the present invention have high strength and a critical thickness reduction rate at break, and also have excellent ductility and shear workability. In addition, it can be seen that the hot-rolled steel sheets according to the examples of the present invention, which have an average crystal grain size of less than 3.0 μm in the surface layer, have excellent resistance to internal bending cracking in addition to the above-mentioned properties. On the other hand, it is found that the hot-rolled steel sheets according to the comparative examples are deteriorated in at least one of strength, ductility, critical sheet thickness reduction rate at fracture, and shear workability. [Industrial Applicability]

[0118] According to the above-mentioned aspect of the present invention, it is possible to provide a hot-rolled steel sheet having high strength and a critical thickness reduction rate at fracture as well as excellent ductility and shear workability. Also, according to the above-mentioned preferred aspect of the present invention, it is possible to obtain a hot-rolled steel sheet having the above-mentioned properties and further suppressing the occurrence of internal cracks in bending, i.e., having excellent resistance to internal cracks in bending. The hot-rolled steel sheet according to the present invention is suitable as an industrial material used for automobile parts, machine structural parts, and further building parts.

Claims

1. The chemical composition, in mass%, is C: 0.050-0.250%, Si: 0.05-3.00%, Mn: 1.00-4.00%, sol. Al: 0.001 to 2.000%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Ti: 0 to 0.500%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0-2.00%, Cr: 0-2.00%, Mo: 0-1.00%, Ni: 0-2.00%, B: 0 to 0.0100%, Ca: 0-0.0200%, Mg: 0 to 0.0200%, REM: 0-0.1000%, Bi: 0 to 0.0200%, As: 0 to 0.100%, Zr: 0 to 1.00%, Co: 0-1.00%, Zn: 0 to 1.00%, W: 0-1.00%, Sn: 0 to 0.05%, and The balance is Fe and impurities. Satisfying the following formulas (A) and (B), The metal structure is, in area percent, The retained austenite is less than 3.0%; Ferrite is 15.0% or more and less than 60.0%; Pearlite is less than 5.0%; The entropy value, which is obtained by analyzing the SEM image of the metal structure by a gray level co-occurrence matrix method and is represented by the following formula (1), is 10.7 or more, The inverse differencing normalized value represented by the following formula (2) is 1.020 or more, The Cluster Shade value represented by the following formula (3) is −8.0×10 5 ~8.0 x 10 5 and The standard deviation of the Mn concentration is 0.60 mass% or less; Tensile strength is 980 MPa or more A hot-rolled steel sheet characterized by: 0.060%≦Ti+Nb+V≦0.500%…(A) Zr+Co+Zn+W≦1.00%…(B) In the formulas (A) and (B), each element symbol indicates the content of the element in mass %, and 0% is substituted when the element is not contained. Here, P(i,j) in the following formulas (1) to (5) is a gray level co-occurrence matrix, L in the following formula (2) is the number of possible gray scale levels of the SEM image, i and j in the following formulas (2) and (3) are natural numbers from 1 to L, and μ in the following formula (3) is x and μ y are represented by the following formulas (4) and (5), respectively. [0010] [0025] [0030] [0045] [0050]

2. The hot-rolled steel sheet according to claim 1, characterized in that the average crystal grain size of the surface layer is less than 3.0 µm.

3. The chemical composition, in mass%, Ti: 0.001 to 0.500%, Nb: 0.001-0.500%, V: 0.001-0.500%, Cu: 0.01-2.00%, Cr: 0.01-2.00%, Mo: 0.01-1.00%, Ni: 0.01-2.00%, B: 0.0001 to 0.0100%, Ca: 0.0001-0.0200%, Mg: 0.0001-0.0200%, REM: 0.0001-0.1000%, Bi: 0.0001-0.0200%, As: 0.001 to 0.100%, Zr: 0.01 to 1.00%, Co: 0.01 to 1.00%, Zn: 0.01-1.00%, W: 0.01 to 1.00%, and Sn: 0.01~0.05% Contains one or more selected from the group consisting of The hot-rolled steel sheet according to claim 1 or 2.

Citation Information

Patent Citations

  • Hot rolled steel sheet

    JP2015098629A

  • Hot rolled steel sheet and production method therefor

    JP2015214718A

  • 700mpa high strength hot rolling q&p steel and manufacturing method thereof

    WO2014166323A1

  • Hot-rolled steel sheet and production method therefor, cold-rolled steel sheet and production method therefor, production method for cold-rolled annealed steel sheet, and production method for hot-dip galvanized steel sheet

    WO2020044445A1

  • Hot-rolled steel sheet

    WO2020184372A1